2013
DOI: 10.1007/s00784-013-1059-3
|View full text |Cite
|
Sign up to set email alerts
|

An early oral health care program starting during pregnancy—a long-term study—phase V

Abstract: Prevention programs starting during pregnancy may establish an improved health behavior. Caries, periodontitis, and dietary complications in mother and child can be avoided by improving maternal oral health and by a tooth-friendly diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 26 publications
0
55
1
9
Order By: Relevance
“…However, only 5% of the affected population had fillings, indicating that almost 95% had no dental treatment for some reason. Studies reveal that dentists are sometimes reluctant to treat pregnant women for various reasons, such as the fear of harming the fetus, fear of litigation or patient safety concern (14,25).…”
Section: Tooth-brushingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only 5% of the affected population had fillings, indicating that almost 95% had no dental treatment for some reason. Studies reveal that dentists are sometimes reluctant to treat pregnant women for various reasons, such as the fear of harming the fetus, fear of litigation or patient safety concern (14,25).…”
Section: Tooth-brushingmentioning
confidence: 99%
“…Children whose mothers have poor oral health are 5 times more likely to have oral health problems than children whose mothers have good oral health (13). Mothers are the main source of transmissible cariogenic bacteria to their children; it has been shown that Streptococcus mutans of mother and child are phenotypically and genotypically similar (14).…”
Section: Introductionmentioning
confidence: 99%
“…Various interventions using professional prophylaxis (Köhler and Andréen 1994), chlorhexidine and fluoride rinse (Brambilla et al 1998), and xylitol chewing gum Thorild et al 2003;Nakai et al 2010) have been demonstrated as effective for preventing or delaying mother-child transmission of MS. Motivational discussions with mothers also lowered the severity of caries in their children (Weinstein et al 2006;Harrison et al 2012). Therefore, early oral health care was emphasized to include dental preventive measures, ideally antenatal and postnatal, for the mother and child until the age of 3 (Meyer et al 2014). Such early intervention programs that include both antenatal and postnatal phases are effective to reduce ECC (Günay et al 1998;Gomez and Weber 2001) and to produce sustained improvement of oral health until young adulthood (Meyer et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, early oral health care was emphasized to include dental preventive measures, ideally antenatal and postnatal, for the mother and child until the age of 3 (Meyer et al 2014). Such early intervention programs that include both antenatal and postnatal phases are effective to reduce ECC (Günay et al 1998;Gomez and Weber 2001) and to produce sustained improvement of oral health until young adulthood (Meyer et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Gebelik, anne ve çocukların ağız-diş sağlığının geliştirilmesi ve erken çocukluk dönemi çürüklerinin önlenmesi açısından en uygun zaman dilimi olarak görülmektedir. 5,11 Erken çocukluk döneminde en sık görülen kronik hastalık olan diş çürükleri yaşam kalitesine çok büyük zararlar verebilen fiziksel, fonksiyonel ve davranışsal olumsuz sonuçlara yol açmaktadır. 12,13 Neden oldukları ağrı, enfeksiyon ve apseler, iştahsızlık, gastrointestinal bozukluk, malnutrisyon, uykusuzluk gibi sonuçlar büyüme ve gelişmede aksamayı beraberinde getirmekte, geçirilen enfeksiyonlar çocuğun…”
Section: Introductionunclassified